Vibration based assessment of Kalbaskraal rail bridge - Hendricks, Moghammad Sameeg (Department of Civil Engineering, 2017)
The focus on the condition and performance of existing structures has increased due to the growing number of structures approaching or exceeding their design life. The challenges associated with the assessment of existing structures include deterioration, changes in loading conditions, changes in the structures function or the structure reaching the latter portion of its designed service life. In order for authorities to better determine how to deal with existing structures, there must be a coherent means of determining, measuring and benchmarking the current condition and performance of the structure. The current study proposes and demonstrates the integration of a visual based condition assessment with vibration based assessment techniques for railway bridges. The methodology suggests a systematic visual assessment combined with the development of a finite element model which is calibrated by using modal parameters ascertained from vibration based testing. The bridge which was used as a case study was the Kalbaskraal Railway Bridge located in Malmesbury. The proposed methodology consists of the following steps: 1) Initial Assessment 2) Development of a Finite Element Model 3) Detailed assessment and Ambient Vibration Field Testing 4) Analysis of Modal Parameters 5) Calibration of FEM using Modal Parameters 6) Setting up Load Configurations 7) Assessment of structural response 8) Assessment of Serviceability limit state of bridge The overall outcome of the study yielded an effective result in that the conclusions drawn from the outcomes of the methodology correlated well with previous studies on the bridge. The structure under its current operational load of 16ton/axle wagons performed within the allowable serviceability limit state. A proposed increase to 22.5ton/axle loads identified that the bridge would be performing on the boundary or above the allowable serviceability limit state and that retrofitting may have to be considered for the bridge to effectively support the additional load. The results derived from this study can be extremely valuable in the bridge management process as the information on the condition of the bridge can aid bridge authorities in their decision making processes.